Amyloid A amyloidosis in a patient with Caplan's syndrome, with special reference to genetic predisposition. (2nd July 2020) - Nakamura, Tadashi; Shiraishi, Naoki; Morikami, Yasuhiro; Fujii, Hiromi; Yoshinaga, Takeshi
Abstract: Secondary amyloid A (AA) amyloidosis, which is a disorder of protein conformation and metabolism, is an important serious complication of inflammatory diseases, especially rheumatoid arthritis (RA). AA amyloidosis develops when AA fibrils, which are derived from the acute-phase reactant, serum amyloid AA (SAA) protein, in the circulation, are deposited in organs and cause systemic organ dysfunction. Caplan's syndrome, or rheumatoid pneumoconiosis, is a rare type of lung disease in which individuals suffering from RA develop lung nodules that are associated with occupational exposure to silica and coal dust. Confirmation of diagnosing as Caplan's syndrome requires the patient's occupational history, imaging studies, and serology. A 72-year-old male, working as a tunnel construction worker for 38 years, with RA who had both chronic cardiac and renal dysfunction was referred to our hospital. He received a diagnosis of pneumoconiosis about 20 years ago, after which he was also diagnosed with RA. So far we performed medical English literature searches on the combination of Caplan's syndrome with AA amyloidosis; there were no articles in relation to such association. Although RA is one of the most common underlying diseases that occur with AA amyloidosis, our report here is the first description of a case of Caplan's syndrome associated with AA amyloidosis. In this report, we provide details about this rare disease occurring with AA amyloidosis and discuss on the possible pathogenesis of AA amyloidosis from a genetic point of aetiological view.